Developmental screening of three‐year‐old children with sickle cell disease compared to controls. (15th August 2021) - Wang, Winfred; Freeman, Molly; Hamilton, Latacha; Carroll, Yvonne; Kang, Guolian; Moen, Joseph; Smeltzer, Matthew P.; Schreiber, Jane; Heitzer, Andrew M.; Estepp, Jeremie; Aygun, Banu
Summary: We previously found that neurodevelopmental deficits commonly occurred in three‐year‐olds with sickle cell disease (SCD), but clinical significance was uncertain because a comparison group was lacking. Our objective in the current study was to prospectively compare neurodevelopment in three‐year‐old children with SCD to an age‐appropriate control group. The Brigance Preschool Screen II is a neurodevelopmental screening examination which can be administered in 15–20 min. SCD patients (Group 1) were compared with community controls of similar age and ethnicity enrolled in daycare/preschool (Group 2). SCD patients who were receiving hydroxycarbamide treatment were also compared (Group 3). Two hundred forty‐five three‐year‐olds were evaluated: Group 1, 111; Group 2, 114; and Group 3, 20. The below cut‐off rate on the Brigance test was higher in Group 1 (73%) than in Group 2 (61%; P  = 0·04). In multivariate analysis of Group 1 patients, only lower household income and more persons living in the home were independent predictors of this. Patients with SCD and matched controls had high rates of 'failing' the Brigance test. The below cut‐off rate in untreated children with SCD was associated with low household income and increased number of persons living in the home.